Histopathology of Brugia pahangi and plasmodium berghei ANKA co-infection in the gerbil (Meriones unguiculatus) - Junaid, Olawale Quazim; Wong, Kum Thong; Khaw, Loke Tim; Mahmud, Rohela; Vythilingam, Indra (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Co-infection with multiple different parasites is a common phenomenon in both human and animals. Among parasites that frequently co-infect the same hosts, are the filarial worms and malaria parasites. Despite this, the mechanisms underlying the interactions between these parasites is still relatively unexplored with very few studies available on the resulting pathologies due to co-infection by filarial nematodes and malaria parasites. Hence, this study investigated the histopathological effect of Brugia pahangi and Plasmodium berghei ANKA (PbA) infections in gerbil host. Gerbils grouped into B. pahangi-infected, PbA-infected, B. pahangi and PbA-coinfected, and uninfected control, were necropsied at different time points of post PbA infections. Brugia pahangi infections in the gerbils were first initiated by subcutaneous inoculation of 50 infective larvae, while PbA infections were done by intraperitoneal injection of 10 6 parasitized red blood cells after 70 days patent period of B. pahangi. Organs such as the lungs, kidneys, spleen, heart and liver were harvested aseptically at the point of necropsy. There was significant hepatosplenomegaly observed in both PbA-infected only and coinfected gerbils. The spleen, liver and lungs were heavily pigmented. Both B. pahangi and PbA infections (mono and co-infections) resulted in pulmonary edema, while glomerulonephritis was associated with PbA infections. The presence of both parasites induced extramedullary hematopoiesis in the spleen and liver. These findings suggest that the pathologies associated with coinfected gerbils were synergistically induced by both B. pahangi and PbA infections.